Mindfulness Moderates Consumer Response to Loud vs. Quiet Luxury Advertising: Status by Design - Errmann, Amy; Voyer, Benjamin; Giroux, Marilyn (Informa UK Limited, 2026)
As demand for “quiet” luxury grows, advertisers face a strategic question: how prominently should brand markers be displayed? Across five studies (N = ∼2,000), we show that the effectiveness of brand prominence depends on consumer mindfulness. When mindfulness is low, prominent logos reinforce extrinsic status motives and increase preference for loud luxury. When mindfulness is high, subtle branding aligns with intrinsic, self-congruent motives and increases preference for quiet luxury. The findings offer an actionable targeting principle: match logo prominence to contextual and behavioral signals of consumers’ inward- versus outward-oriented status motives.
Keywords: 35 Commerce, Management, Tourism and Services; 3506 Marketing; Complementary and Integrative Health; Behavioral and Social Science; 1505 Marketing; 2001 Communication and Media Studies; Marketing; Brand prominence; luxury consumption; mindfulness; motivation; status consumption; luxury advertising